The Student Exchange Program as an Effort to Optimize Indonesian Language Learning in Thailand - Familia, Ni Putu Echa; Sudirman, I Nyoman; Petsong, Juttalee (The Future of Education Journal, 2025)
The student exchange program is one of the valuable academic experiences as it not only broadens perspectives but also opens opportunities to interact directly with the culture, language, and daily life of people in other countries. In this activity, I, as a student from the Markandeya Bali Institute of Technology and Education, had the opportunity to teach Indonesian language in Thailand as part of an effort to introduce the Indonesian language and culture to foreign students. The main objective of this activity was to help Thai students understand and use Indonesian in a fun, communicative way, and in accordance with their needs at the initial stage of learning. The learning process was carried out using a communicative approach through visual media, language games, and conversation exercises, enabling students to understand the meaning and contextual use of the language. The results of the activity showed very positive development. Students became more confident in speaking Indonesian and were able to grasp basic vocabulary well. The interactive learning atmosphere also sparked their enthusiasm in learning about Indonesian culture. In addition to benefiting the students, this activity also provided a valuable experience for me as a future educator in understanding cultural differences in learning and the challenges of cross-language communication. This experience emphasizes that language education is not only about mastering linguistics but also plays a role as a bridge to strengthen international relations and foster mutual respect through educational diplomacy.